2020
DOI: 10.3390/biom10060958
|View full text |Cite
|
Sign up to set email alerts
|

The Hyperoxic-Hypoxic Paradox

Abstract: Effective metabolism is highly dependent on a narrow therapeutic range of oxygen. Accordingly, low levels of oxygen, or hypoxia, are one of the most powerful inducers of gene expression, metabolic changes, and regenerative processes, including angiogenesis and stimulation of stem cell proliferation, migration, and differentiation. The sensing of decreased oxygen levels (hypoxia) or increased oxygen levels (hyperoxia), occurs through specialized chemoreceptor cells and metabolic changes at the cellular level, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
160
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 136 publications
(166 citation statements)
references
References 121 publications
(165 reference statements)
4
160
0
2
Order By: Relevance
“…Similar to the current study, a previous prospective one-year observational study in divers exposed to intense hyperbaric oxygen, showed significant telomere elongation in leukocytes [ 31 ]. As used in the current study, the HBOT protocol utilizes the effects induced by repeated intermittent hyperoxic exposures, the so called hyperoxic hypoxic paradox [ 13 , 18 ]. These intermittent hyperoxic exposures induce an adaptive response which includes increased upregulation of antioxidants genes [ 32 ] and production of antioxidants/scavengers that adjust to the increased ROS generation causing the ROS/scavenger ratio to gradually becomes similar to the ratio under a normal oxygen environment.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Similar to the current study, a previous prospective one-year observational study in divers exposed to intense hyperbaric oxygen, showed significant telomere elongation in leukocytes [ 31 ]. As used in the current study, the HBOT protocol utilizes the effects induced by repeated intermittent hyperoxic exposures, the so called hyperoxic hypoxic paradox [ 13 , 18 ]. These intermittent hyperoxic exposures induce an adaptive response which includes increased upregulation of antioxidants genes [ 32 ] and production of antioxidants/scavengers that adjust to the increased ROS generation causing the ROS/scavenger ratio to gradually becomes similar to the ratio under a normal oxygen environment.…”
Section: Discussionmentioning
confidence: 99%
“…These intermittent hyperoxic exposures induce an adaptive response which includes increased upregulation of antioxidants genes [ 32 ] and production of antioxidants/scavengers that adjust to the increased ROS generation causing the ROS/scavenger ratio to gradually becomes similar to the ratio under a normal oxygen environment. However, because the scavenger elimination half-life (T 1/2 ) is significantly longer than the T 1/2 of ROS, upon return to normoxia, following repeated hyperoxic exposures, there are significantly higher levels of scavengers and increased antioxidant activity [ 13 , 18 ]. Thus, similar to physical exercise and caloric restriction, a daily repeated HBOT protocol can induce the hormesis phenomenon.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations